UiTM Sarawak receives masks from AHMU and ACEC association - Chung, Ellen (UiTM Sarawak, 2021)
COVID-19 has wreaked havoc to all walks of life globally. At a time when we were desperately in need of facial masks to provide some form of protection against this lethal disease, our partner in China, Anhui Medical University, together with Asia China Education and Culture (ACEC) Association had generously donated 600 pieces ofKN95 masks to UiTM Sarawak. These masks were handed over to Rector, Professor Dato Dr. Jamil bin Haji Hamali at Kampus Samarahan on 13th May 2020